2021
DOI: 10.1515/noise-2021-0012
|View full text |Cite
|
Sign up to set email alerts
|

Rio de Janeiro noise mapping during the COVID-19 pandemic period

Abstract: This paper presents a comparison between the acoustic scenario at the Rio de Janeiro city center, before and during the COVID-19 pandemic. Undergoing one of the most important pandemics of the recent history, the social isolation led to a new acoustic scenario for Rio de Janeiro. The study was realized at the city center, an area of historical, economic and cultural relevance. The comparison consisted of analyzing measured data and noise maps produced for the city center area. The maps were created according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…Noise levels in three Boston, USA, urban protected areas were measured before, during, and after emerging from COVID-19 lockdown, which revealed lower noise levels occurred at two of the parks due to less traffic ( Terry et al, 2021 ). Similar declines in urban noise levels have been reported in various locations globally, for example, in Stockholm, Sweden ( Rumpler et al, 2020 ), Rio de Janeiro, Brazil ( Gevú et al, 2021 ), and Barcelona, Spain ( Bonet-Solà et al, 2021 ). COVID-19 also leads to months-long reduction in seismic noise, providing a valuable window for researchers to detect subtle signals from subsurface seismic sources and make benchmark limits of anthropogenic sounds ( Lecocq et al, 2020 ).…”
Section: Short-term Positive Impacts Of Covid-19 On the Environmentsupporting
confidence: 76%
“…Noise levels in three Boston, USA, urban protected areas were measured before, during, and after emerging from COVID-19 lockdown, which revealed lower noise levels occurred at two of the parks due to less traffic ( Terry et al, 2021 ). Similar declines in urban noise levels have been reported in various locations globally, for example, in Stockholm, Sweden ( Rumpler et al, 2020 ), Rio de Janeiro, Brazil ( Gevú et al, 2021 ), and Barcelona, Spain ( Bonet-Solà et al, 2021 ). COVID-19 also leads to months-long reduction in seismic noise, providing a valuable window for researchers to detect subtle signals from subsurface seismic sources and make benchmark limits of anthropogenic sounds ( Lecocq et al, 2020 ).…”
Section: Short-term Positive Impacts Of Covid-19 On the Environmentsupporting
confidence: 76%
“…The London study showed that active areas were affected the most, followed by traffic-dominated areas and quiet areas. Similar trends were found in Madrid, although less pronounced (Asensio, Pavón, and de Arcas, 2020) or into the Brazilian study (Gevú, Carvalho, Fagerlande, Niemeyer, Cortês, and Torres, 2021), which complements its measurements with modeling approach. These slight discrepancies between the two studies may be due to a different classification between the site categories.…”
Section: Introductionsupporting
confidence: 80%
“…First, cities equipped with noise measurement networks, capturing continuous noise levels, have been quick to consistently point out the drop in the noise levels. An equivalent sound level reduction of about 4–7 dB(A) has been reported, on average, in Rio ( Gevú et al , 2021 ), Montreal ( Steele and Guastavino, 2021 ), Lyon ( Munoz et al , 2020 ), Madrid ( Asensio et al , 2020b ), Milan ( Zambon et al , 2021 ), Girona ( Alsina-Pagès et al , 2021 ), or Paris ( Bruitparif, 2020 ) based on 21 to more than 100 fixed sensors. Numerous short-term measurements were performed in London in Aletta et al (2020) through a series a 30-s binaural recordings pre-lockdown and during the lockdown (481 samples) at 11 locations, which highlighted a similar tendency.…”
Section: Introductionmentioning
confidence: 98%
“…The findings call attentions on massive noise exposure near transportation-related communities. Gevú et al [ 29 ] compared noise level in pre- and during the COVID-19 pandemic and related comparative factors in Rio de Janeiro, Brazil, and compromised several noise maps based on the noise datasets and related variables. The study found a ten dBA reduction during the COVID-19 period, with the building height as a variable in noise level reduction.…”
Section: Building Material/shape/geometrymentioning
confidence: 99%